EXPANSION OF OPPORTUNITIES OF THE FLOW CYTOMETRY METHOD FOR CLINICAL AND IMMUNOLOGYCAL PRACTICE - S. V. Khaidukov; A. V. Zurochka (Медицинская иммунология)
Abstract. The purpose of this article was to make a broad audience of experts familiar to new developments in the method of flow cytometry that have found applications in medical and biologic studies, in order of their further implementation into everyday practice. These applications include the following approcahes: detection of antigen-specific T-cells by using of tetramer technology, flow cytometric determination of cytokines in biological liquids, determination of in vitro sensitivity of basophilic granulocytes to allergen effects, detection of Th1 and Т-reg cells by their cell surface markers. When using multiparametric analysis, a multi-step gating and other new technologies, the flow cytometry technique allows of location and tracing the majority of processes occurring in development of immune response. When studying these dynamic events, we get an opportunity to react adequately to apropriate changes, and to develop new approaches to correct altered cellular activities, that they should determinate.